Chhaupadi and Education of girls: a study on effects of Chhaupadi practice on education of adolescents girls in Karnali. - Dahal,Bhola Prasad (2017)
SUMMARY: Menstruation is a woman's monthly bleeding which usually takes/marks as the switching from a girlhood to the womanhood. It mostly starts between the age of 11-15 years of their lives and continues till the age of 50 years. When a female countenance this menstruation, they face various physical changes like body shapes, fluctuations in hormone levels, painful cramps during menstruation period, and muscle contractions etc. They also face social and cultural obligations in some hilly and mountainous districts of Mid and Far-west Regions of Nepal. It is traditionally believed and culturally practiced that women are impure during their menstruation periods and are not allowed to participate in normal daily activities. Hence, this natural process become curse for many adolescent girls and women. Chhau means few restrictions on food, mobility, religious functions and shelter to women and adolescent girls during mensuration which is common in Nepalese society. Chhaupadi is a system and practice of putting women and adolescent girls outside the house in a Cow-shed or in a separate small and dark Chhau-gotha in Mid and Far West Regions.It was found that: i) nuclear family has less restriction than the joint family; ii) female members are stricter than the male members of the family; iii) grandparents are stricter than other members; iv) daughters have more flexibility than daughter-in-law; v) semi-urban and urban areas are flexible than rural areas; vi) mix communities are more open than homogenous community; vii) family with migrant members are less restrictive; and viii) family of religious leaders and priests are more restrictor. In such condition, it demands engagement and collaboration of human rights and social development agencies with Academia for a proper research and studies on it. Working together may bring changes but deeply rooted socio-cultural normsand practices leave a big question mark on societal transformation. This does not only affect the regular activities of the female but also has effect in their education. The purpose of the study was to assess the real status of Chhaupadi and its effects on life of women and adolescent girls. The research team believes that this type of study itself brings changes in communities, documents the existing Chhaupadi norms and practices and also guidestoset future priorities and interventions. Therefore, keeping this in mind, the researchcovered the school/college (not) going adolescent girls from 11 to 25 years of age in Jumla, Mugu and Kalikot districts. This research work is a part of the project, "Elimination of Chhaupadi practice in Karnali, Nepal", implementing by Action Works Nepal (AWON) and Bheri Environmental Excellence (BEE) Group with the funding from European Commission. The five-member study team applied both the quantitative and qualitative methodologies on this research. The data and information was collected from survey questionnaire, focused group discussions, key informant interviews and observations. The research was carried out in 7 VDCs each from Jumla, Mugu and Kalikot. There were 21 field enumerators and six research assistants in total who received 5 days training on research tools, methods and questionnaire. The research team itself visited all three districts and seven VDCs in total for supervision of the field study and also to interact and carry out FGDs for in-depth information. The project team in both organizations provided logistic support to research team and to coordinate with stakeholders for both the quantitative data and qualitative information. In regard to Chhaupadi and its effect in Education, there were altogether 616 respondents selected randomly from three research districts (altogether 21VDCs) with different caste and ethnicity. Among respondents, there were 75.6% school/college going respondents, 20.3% were dropped/left out and 4.1% have never attended school. The findings revealed that 94%respondents attended school during menstruation period, but those who remained absent on those days take leave mostly on the first day of menstruation (8.3%) and the absent rate decreases as the days of menstruation increases from 6.9% in second day to 0.2% in eighth day. There were altogether 233 participants (37.8%) who do not attend school during menstruation (including school left, never attended and absent during menstruation). Nearly 20% do not attend school because of health problem during menstruation and 19% responded that they felt uneasy to go, where 16% remained absent cause of shyness on those days. And still 15% have to stay in separate place strictly in those days so they remain at home, and in the same way other 5% were not allowed by parents to attend school. The reason behind leaving the school on the first day of menstruation is because of not having proper facilities at school. Not only this, the restriction of touching and crossing the temples has also stopped them to be regular in school on those days. Not only the Chhau-Goth affects the study, the myth of not touching books during that period also hinders them. Similarly, Chhaupadi tradition is being one of the reasons of increasing drop-out rates(20% in researched VDCs) in education. Furthermore, the data shows that lack of education is not only a cause of continuing that tradition. The participants admitted that the stay in Chhau-Goth should be eliminated but touching gods and cooking at that time most not be eliminated along with Chhau-Goth system. As the participants seemed afraid of it as they still believe it can bring violence in the community. But still pointing only on the education system or showing the cause of lack of education on practicing this Chhaupadi tradition seems to be a myth as most of the people are aware but to change the mind-set of the local people on their strong beliefs on deep-rooted traditions is a challenge. Educated people who are in Kathmandu valley or in other cities also do follow Chhaupadi system while going back home. The politicians and government officials are also strictly following this. Adolescent girls critically raised this double standards and practices of authorities which makes continuity of such practices. Thiscan only be solved with the continuous effort of multi-sector involvement which requires a lot of patience.Most participants accept that this culture should be avoided, but still are following as they have fear to their elders and myths created on the culture. Similarly, most of the respondents mentioned that school teachers also are continue this practices both in schools and at home. It is because of respect and habit from childhood to continue the culture, mostly the male Nepali teachers who are considered as Bahuns stay far from females though they do not speak on that.And when adolescent girlsmiss the classes by staying absent in menstruation period, 79% feel difficult to consult teachers, even 4% aloud that teachers are not cooperative and there is not such practice developed (17.4%) to ask them for extra support for those missing days. This shows the gap and mistrust between teachers and students. Until we can not make school child friendly girls can not talk openly with teachers. Furthermore, the school Actors for Campaign on Chhaupadi elimination are limited on preaching and lacking on practicing as teachers themselves follow this practice in school.However, most of the community leaders, traditional healers and school teachers are aware and agreed to eliminate the system of staying in cow-shed; but still considered menstruationtime as impure and are not allowed to touch temples and kitchen. Hence, elimination of Chhaupadi is limited to elimination of Chhau-Goth but not of other untouchability. It was also found that female counter parts were more rigid to continue the tradition than male counterparts. The Chhaupadi system is being taken as a culture from several years, so one cannot think to eliminate it with few interventions in small span of time. From the immense study in the project area, the research team recommends that there should be a course on school curriculum regarding menstruation and reproductive health as a natural and biological aspect, not as the impure or untouchability by god. School education should focus more on menstrual hygiene to eliminate this practice.